Synthesis and Flame Retardant Properties of Low Density Polyethylene/Ethylene-Vinyl Acetate/Polyphosphazene Derivative Composites - Zhao, Zhengping; Zhou, Zeping; Yu, Fengying; Ji, Jianbing (Asian Journal of Chemistry, 2015)
Polyphosphazene derivative, hexaphenoxylcyclotriphosphazene, was synthesized via hexachlorocyclotriphosphazene and phenol by nucleophilic substitution as a kind of intumescent fire retardant filling with ethylene-vinyl acetate copolymer, Mg(OH)2 and Al(OH)3 to modified low density polyethylene to study the effects of content and different polyphosphazene structure on the flame retardant properties. The LOI value increased from 17.0 to 22.2 with the hexaphenoxylcyclotriphosphazene individually. But, when composited with Mg(OH)2, Al(OH)3, the blends have better flame retardancy. The LOI value was 31.7 at the filling amount of 5 wt. % hexaphenoxylcyclotriphosphazene (M-3) and changing characteristics from V-2 (flammable material) to V-0 (flame retardant material). The maximum specific optical density decreased from 370.65 to 91.72 and the maximum flame retardant synergist index reached 3.4. SEM morphology of smoke density residue shows that hexaphenoxylcyclotriphosphazene promotes the increase of residual volume and compactness of surface layer of the solid residues.